Working conditions, vocal health and work ability in teachers: an integrative review - Harold Zamir Taborda-Osorio; Luis Miguel Cárdenas-Castellanos (Iberoamerican Journal of Medicine)
Introduction: Work Ability (WA) is the balance between job demands and a worker's individual resources to satisfy those demands. Teachers who have health problems related to musculoskeletal disorders (MSD) and respiratory diseases (RD) have their WA affected. Objective: To understand the relationship between working conditions, vocal health, and WA in teaching work according to literature. Methods: An integrative review was carried out with a search of the scientific literature in 7 databases: Medline Complete, Proquest, Pubmed, Sciencedirect, Scopus, Virtual Health Library (VHL) and Web of Science (WOS). Original studies in Spanish, English and Portuguese related to the topic were included. Results: 7 studies were analyzed in this review. Results show Giannini and Vertanen-Greis as the main authors who have published about the topic. 100% of the studies of this review have investigated the topic in primary and secondary teachers. Teachers with voice problems are almost three times more likely to lose their WA than those without voice problems, and there is a stronger association between loss of WA and voice problems. Conclusions: Studies related to working conditions, vocal health and WA in teaching work are recent and the evidence is scarce. To date, greater decreases in WA have been found in teachers who report high levels of stress, poor air quality, and have a diagnosed voice problem.